Intervenção do banco central no mercado interbancário - Aveiro, João Paulo Carvalho (2012)
In this work, we studied the literature of the interbank market and how a central bank can improve its functioning. We developed a framework that could accommodate the different models of the interbank market and central bank intervention created from Bryant (1980) and Diamond and Dybvig (1983). With this we show that, in most cases, banks with access to the interbank market are unable to provide the efficient allocation for its consumers. In this environment we find a role for a central bank that, by intervening in the interbank market, is able to induce banks to offer the same allocations that would be provided by a social planner, that is, efficient allocations.